2008
DOI: 10.1021/jo8004827
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Natural Product Scaffolds by Acyl- and Arylnitroso Hetero-Diels−Alder Reactions: New Chemistry on Piperine

Abstract: Piperine, a natural product containing a conjugated diene, was reacted with polymer-supported acyl- and arylnitroso dienophiles. The reactions with arylnitroso dienophiles were also carried out in solution. The oxazine rings formed by the corresponding hetero-Diels-Alder reactions were further transformed and novel acyclic as well as heterocyclic derivatives including pyrroles and quinoxalinones were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…4 a Clearly, 6-methyl-2-nitrosopyridine 4a , as a stabilized form of iminonitroso reagent, constitutes an ideal combination of reactivity and stability for NDA reactions with leucomycin A7, relative to benzenenitroso 2 and acylnitroso agent 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 a Clearly, 6-methyl-2-nitrosopyridine 4a , as a stabilized form of iminonitroso reagent, constitutes an ideal combination of reactivity and stability for NDA reactions with leucomycin A7, relative to benzenenitroso 2 and acylnitroso agent 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our effort in this area has involved nitroso Diels–Alder (NDA) reactions as efficient methods for derivatization and functionalization of diene-containing natural products. 4 Our early research has demonstrated that several complex diene-containing natural products, including leucomycin A7 5 (also known as turimycin H3) (Fig. 1), readily undergo nitroso cycloadditions, generating 1-amino-4-hydroxy-2-ene heterocycle scaffolds with high regio- and stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[182] Piperin (177), eine der Hauptkomponenten von Pfeffer, reagierte mit polymergebundenen Nitrosocarbonylspezies nach Entschützen zu den Cycloaddukten 178 und 179 (Schema 32). [183] Die Autoren waren überrascht darüber, dass bei der Behandlung mit TFA und Triethylsilan zum Abfangen von Kationen aus 178 das Hydroxylamin 180 entstand. Unter den gleichen Bedingungen wurde das Cycloaddukt 179 unverändert aus dem Reaktionsgemisch zurückgewonnen.…”
Section: Derivatisierung Von Naturstoffenunclassified
“…Krchnak and co-workers 27 described the synthesis of new pyrrole and quinoxalinone analogues. The strategy involved the cycloaddition of piperine, a natural conjugated diene, with polymer supported acyl-and arylnitroso dienophiles 136 (Scheme 19).…”
Section: Lee and Parkmentioning
confidence: 99%